Becoming a Teacher on the Job: The Hidden Socialization of Untrained Teachers - Gagne, Allison; Morrissette, Joëlle (Proceedings of the International Conference on Networked Learning, 2026)
Across many education systems, the growing teacher shortage has led schools to rely increasingly on individuals who have not completed formal teacher training. While quantitative studies have explored teacher attrition, motivation, and efficiency, far less is known about how untrained teachers become familiar with their professional role when they enter schools. Grounded in an interactionist perspective (Becker, 1982; Schön, 1983) and theories of professional socialization (Doucet & Viviers, 2016; Lima, 2015), this doctoral study examines how teachers without pedagogical training are socialized to their professional role within the complex social world of schools. Methodologically, the project adopts a collaborative research approach (Morrissette, 2013). Through facilitated discussion groups, untrained and trained teachers will be invited to collectively reflect on situations drawn from their everyday work (Chell, 1998; Mucchielli, 1968). This collective inquiry will not only generate empirical data, but create a space for professional critical reflection, positioning research as a resource for ongoing professional learning. By focusing on processes rather than outcomes, this study addresses both empirical and methodological gaps in the literature. It sheds light on how untrained teachers become familiar with their role in contexts characterised by limited institutional support. More broadly, it raises questions about what it means to become a teacher today, at a time when professional socialization increasingly occurs outside traditional teacher education pathways.